A new cure kinetics model to simulate thermomechanical behavior of polymeric sealants for automotive applications. (16th December 2021) - Choi, Jae-Hyuk; Shim, Wonbo; Rhie, Chul Hong; Yu, Woong-Ryeol
Abstract: Accurate prediction of the cure level of thermoset polymers is essential to simulate the thermomechanical behavior of polymeric thermoset sealants, which is strongly dependent on cure level. Conventional cure kinetics models, however, fail to accurately predict the cure levels of thermoset sealants subjected to a complex temperature program. Herein, we propose a new cure kinetics model that greatly enhances cure level predictability by considering temperature derivatives. The validity of our model was verified by simulating the thermomechanical behavior of a polymeric sealant using a user material subroutine (UMAT) of ABAQUS software. Experimental results from an appropriately designed thermomechanical test were compared with simulation results obtained from the UMAT.